Fine-scale GPS tracking to quantify human movement patterns and exposure to leptospires in the urban slum environment. - Katharine A Owers; Juliana Odetunde; Rosan Barbosa de Matos; Gielson Sacramento; Mayara Carvalho; Nivison Nery; Federico Costa; Mitermayer G Reis; James E Childs; José E Hagan; Peter J Diggle; Albert I Ko (Public Library of Science (PLoS), 2018)
BACKGROUND:Human movement is likely an important risk factor for environmentally-transmitted pathogens. While epidemiologic studies have traditionally focused on household risk factors, individual movement data could provide critical additional information about risk of exposure to such pathogens. We conducted global positioning system (GPS) tracking of urban slum residents to quantify their fine-scale movement patterns and evaluate their exposures to environmental sources of leptospirosis transmission. METHODOLOGY/PRINCIPAL FINDINGS:We recruited participants from an ongoing cohort study in an urban slum in Brazil and tracked them for 24 hours at 30-second intervals. Among 172 subjects asked to participate in this cross-sectional study, 130 agreed to participate and 109 had good quality data and were included in analyses. The majority of recorded locations were near participant residences (87.7% within 50 meters of the house), regardless of age or gender. Similarly, exposure to environmental sources of leptospirosis transmission did not vary by age or gender. However, males, who have higher infection rates, visited a significantly larger area during the 24-hour period than did females (34,549m2 versus 22,733m2, p = 0.005). Four male participants had serologic evidence of Leptospira infection during the study period. These individuals had significantly larger activity spaces than uninfected males (61,310m2 vs 31,575m2, p = 0.006) and elevated exposure to rodent activity (p = 0.046) and trash deposits (p = 0.031). CONCLUSIONS/SIGNIFICANCE:GPS tracking was an effective tool for quantifying individual mobility in the complex urban slum environment and identifying risk exposures associated with that movement. This study suggests that in addition to source reduction, barrier interventions that reduce contact with transmission sources as slum residents move within their communities may be a useful prevention strategy for leptospirosis.